Amending woodchip bioreactors with corncobs reduces nitrogen removal cost. (15th March 2023) - Law, Ji Yeow; Slade, Alexis; Hoover, Natasha; Feyereisen, Gary; Soupir, Michelle
Abstract: Woodchip denitrification bioreactors are an effective agricultural practice to reduce nitrogen (N) export from subsurface drainage via the conversion of nitrate (NO3 − ) to nitrogen gas (N2 ), but there are challenges associated with limited woodchip supplies and increasing prices. Previous lab studies indicate that corncobs could be a promising woodchip alternative from the perspectives of N removal rate and cost. This field study aimed to provide early performance and cost assessment of denitrification bioreactors with two woodchip-corncob treatments. The objectives were to i) compare N removal rates of bioreactors with different carbon and hydraulic retention time (HRT) treatments, ii) compare bioreactor N removal costs, and iii) conduct sensitivity analysis on full-scale bioreactors (FBR) N removal costs with varying corncob lifespans and prices. Nine replicated field pilot-scale bioreactors (PBRs) using three carbon treatments and three HRTs were assessed for N removal efficiency. The carbon treatments were woodchip-only (WC100), 25% (by vol.) corncobs + 75% woodchips media (CC25) in series, and 75% corncobs + 25% woodchips (CC75) in series set at HRTs of 2, 8, and 16 h. N concentrations were monitored at each PBR inlet and outlet, and the PBR N removal efficiencies were used to estimate FBR N removal rates and costs. At respective HRTs, the estimated N removal rates of CC75 were 1.6- to 10.1-fold higher than WC100, but CC25 exhibited 0.9-fold lower (at 8-hr HRT) to 2.8-fold higher than WC100. A 15-yr cost assessment indicated CC75 (10.56 to 13.89 kg −1 N) was the most cost-efficient treatment, followed by WC100 (13.30 to 88.11 kg −1 N) and CC25 (22.41 to 60.13 kg −1 N). This assessment showed CC75 as a promising alternative to WC100 in terms of N removal rate and cost, but CC25 did not provide sufficient N removal rate increase for it to be a cost-efficient option. Nonetheless, using corncobs as a bioreactor medium is a relatively new approach, and we encourage more field studies to explore the long-term opportunities and challenges. Graphical abstract: Image 1 Highlights: Corncob-amended woodchip bioreactors improved nitrate removal rates. The material cost for corncobs was lower than woodchips. Corncobs have a shorter expected lifespan, thus requiring frequent replacement. Bioreactors filled with corncobs could reduce nitrogen removal costs.